(untitled) (Journal of Philosophy, Culture and Political Science, 2025)
This article examines some aspects of the introduction of network and digital technologies into our lives. This study aims to analyze the impact of introducing network and digital technologies on individual and social life, as well as on the formation of value orientations and ethical norms. The results of this study help us understand how digital reality affects identity, values, and social relations, which is crucial for developing strategies to adapt and regulate technologies in society. The article applies a comprehensive analysis of existing theoretical approaches to networking and digital reality and their impact on value systems; conceptual methods are used to identify changes in ethics and social structure. It is revealed that virtual identities and new values form a digital civilization that gradually replaces real values, causing a transformation of public consciousness and being. Conflicts between offline values and virtual counterparts, as well as processes of displacement of true values by false ones, are discovered. The findings show how the introduction of digital technologies leads to significant changes in the value orientations of humans and society, which requires a conscious approach to managing these processes to preserve cultural and ethical foundations. The value of the study lies in the in-depth understanding of the processes of value transformation in the era of digitalization, which contributes to the development of recommendations for harmonizing the virtual and real spheres of life, as well as for the formation of responsible use of technologies. Key words: man, digital technologies, network identity, ethical values, virtual reality.